Synthesis and Characterization of Chitosan/Phosphotungstic Acid-Montmorillonite Modified by Silane for DMFC Membrane - Dian Permana; Muhammad Purwanto; La Ode Ahmad Nur Ramadhan; Lukman Atmaja (Indonesian Journal of Chemistry, 2015)
Montmorillonite was functionalized by (3-glycidyloxypropyl) trimethoxy silane (GPTMS). Subsequently, chitosan (CS) membranes filled by GPTMS-modified montmorillonite particles were prepared and characterized by FTIR. The result of FTIR obtained the peak wavenumber of 2940, 1471 and 1390 cm-1 referring to vibration stretching of CH2, bending of CH2 and CH3 form epoxy groups in silane, respectively which indicated modification of montmorillonite by silane. Compared with the pure CS and CS/PWA-MMT membrane, these CS/PWA-MMT/Silane hybrid membranes show apparently high proton conductivity and the lower methanol permeability, which could be assigned to the better interfacial morphology and compatibility between chitosan matrix and GPTMS-modified montmorillonite. In all the prepared CS/PWA-MMT/Silane hybrid membranes, the CS membrane filled by 10% GPTMS-modified montmorillonite particles exhibits the highest proton conductivity and the lowest methanol permeability, which is 19.15 x 10-3 S.cm-1 at 80 °C and 4.33 x 10-8 cm2.s-1, respectively. The results imply that CS/PWA-MMT silane 10% membrane has better interaction of interfacial morphology and compatibility between chitosan matrix and GPTMS-modified montmorillonite particles.